2018
DOI: 10.1245/s10434-018-6435-4
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Nomogram to Risk Stratify Patients for the Benefit of Trimodality Therapy in Esophageal Adenocarcinoma

Abstract: PurposeTo develop a nomogram that estimates 1-year recurrence-free survival (RFS) after trimodality therapy for esophageal adenocarcinoma and to assess the overall survival (OS) benefit of esophagectomy after chemoradiotherapy (CRT) on the basis of 1-year recurrence risk.MethodsIn total, 568 consecutive patients with potentially resectable esophageal adenocarcinoma who underwent CRT were included for analysis, including 373 patients who underwent esophagectomy after CRT (trimodality therapy), and 195 who did n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 33 publications
3
19
1
Order By: Relevance
“…This cohort exhibited an early recurrence rate of 29·1 per cent, which is similar to that in previous reports where this outcome was specified explicitly. There was also an R1 resection rate of 28·4 per cent, in line with previously reported data based on an RCP definition of CRM positivity (CRM less than 1 mm is positive).…”
Section: Discussionsupporting
confidence: 86%
“…This cohort exhibited an early recurrence rate of 29·1 per cent, which is similar to that in previous reports where this outcome was specified explicitly. There was also an R1 resection rate of 28·4 per cent, in line with previously reported data based on an RCP definition of CRM positivity (CRM less than 1 mm is positive).…”
Section: Discussionsupporting
confidence: 86%
“…The current study identified gender, poor tumor differentiation grade, signet ring cell adenocarcinoma, baseline clinical nodal status, and SUV max of the initial positron emission tomography/computed tomography as independent prognostic factors for early recurrence after trimodality therapy 3. Based on the subsequent prediction model, patients at high-risk of early recurrence had no survival benefit of trimodality therapy compared with definitive chemoradiotherapy.…”
Section: Presentmentioning
confidence: 86%
“…The primary outcome measure was early recurrence, defined as confirmed local, regional or distant recurrence at less than 1 year from the date of surgery 5,8,13 . Missing Data was treated as being missing completely at random and handled by list wise deletion.…”
Section: Source Of Datamentioning
confidence: 99%